Ring-closing metathesis mediated total synthesis of microcarpalide and herbarumin III - Gurjar, M. K.; Nagaprasad, R.; Ramana, C. V.; Karmakar, S.; Mohapatra, Debendra K. (Arkivoc, 2005)
Total synthesis of naturally occurring microcarpalide and herbarumin III are described. The ring-closing metathesis (RCM) approach to coin the medium sized rings present in their molecular structures form the basic premise of this investigation.
Keywords: herbarumin III; microcarpalide; microfilament; phosphodiesterase; ring-closing metathesis (RCM)